Photocatalytic visible-light active bismuth tungstate coatings deposited by reactive magnetron sputtering. (May 2015) - Ratova, M.; West, G.T.; Kelly, P.J.
Abstract: Photocatalytic bismuth tungstate thin films with visible-light activity were deposited via reactive pulsed DC magnetron sputtering onto soda-lime glass substrates. Varying the power delivered to the bismuth and tungsten targets allowed control over the Bi/W ratio in the coatings, and therefore the structural and optical properties of the coatings. As-deposited coatings were characterised with amorphous microstructures and were annealed at 673 K to develop crystallinity. The visible light photocatalytic activity of the coatings, which was analysed using the methylene blue degradation test, was found to be superior to that of a commercial titania-based photocatalytic product. Highlights: Bismuth tungstate coatings were deposited by magnetron sputtering. Bismuth tungstate coatings are found to be efficient visible light photocatalysts. Bi2 WO6 showed higher visible light activity than the commercial glazing product.